2022
DOI: 10.3389/fphar.2022.896971
|View full text |Cite|
|
Sign up to set email alerts
|

Cefiderocol for the Treatment of Multidrug-Resistant Gram-Negative Bacteria: A Systematic Review of Currently Available Evidence

Abstract: Cefiderocol is a novel synthetic siderophore-conjugated antibiotic that hijacks the bacterial iron transport systems facilitating drug entry into cells, achieving high periplasmic concentrations. This systematic review analyzed the currently available literature on cefiderocol. It summarized in vitro susceptibility data, in vivo antimicrobial activity, pharmacokinetics/pharmacodynamics (PK/PD), clinical efficacy, safety and resistance mechanisms of cefiderocol. Cefiderocol has potent in vitro and in vivo activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 118 publications
1
17
0
Order By: Relevance
“…Susceptibility rates over 90% are also reported for OXA-23- and OXA-24-like producers. However, in vitro studies showed the MICs for New Delhi metallo-β-lactamase (NDM) positive isolates to be significantly higher than those harboring other β-lactamase genes, with a susceptibility rate of 83.4% for cefiderocol [ 90 ]; the expression of NDM appears to facilitate the emergence of cefiderocol resistance by mutations in siderophore receptors [ 91 , 92 ].…”
Section: Available Treatments For Carbapenem-resistant Gram-negative ...mentioning
confidence: 99%
“…Susceptibility rates over 90% are also reported for OXA-23- and OXA-24-like producers. However, in vitro studies showed the MICs for New Delhi metallo-β-lactamase (NDM) positive isolates to be significantly higher than those harboring other β-lactamase genes, with a susceptibility rate of 83.4% for cefiderocol [ 90 ]; the expression of NDM appears to facilitate the emergence of cefiderocol resistance by mutations in siderophore receptors [ 91 , 92 ].…”
Section: Available Treatments For Carbapenem-resistant Gram-negative ...mentioning
confidence: 99%
“…2 Susceptibility surveillance has revealed the potent activity of CFDC against a wide range of carbapenem-resistant gram-negative bacteria (CR-GNB), including isolates of Acinetobacter baumannii, Enterobacterales, and Pseudomonas aeruginosa. 3 The CREDIBLE-CR trial showed that the clinical and microbiological efficacy of CFDC was comparable to that of the best available therapeutic agents for various CR-GNB infections. 4 However, resistance to CFDC has emerged among CR-GNB before its widespread use in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…The emergence and spread of carbapenemase-producing (CP) Gram-negative bacteria (GNB) represent a serious public health problem because effective therapeutic alternatives (e.g., colistin and cefiderocol) are not widely available in lowincome countries. [1][2][3] Therefore, carbapenems remain often the last available antibiotic class to treat infections caused by multidrug-resistant nonfermenter (Acinetobacter baumannii and Pseudomonas aeruginosa) and fermenter (Enterobacterales) GNB. 4,5 Acquired class A (KPC, IMI, GES), class B (IMP, VIM, NDM), and class D (OXA-48, OXA-181) carbapenemases are the most prevalent determinants of resistance to carbapenems.…”
Section: Introductionmentioning
confidence: 99%